District heating by drinking water heat pump: Modelling and energy analysis of a case study in the city of Milan. (1st January 2017) - De Pasquale, A.M.; Giostri, A.; Romano, M.C.; Chiesa, P.; Demeco, T.; Tani, S.
Abstract: This paper investigates the integration of a district heating heat pump for the production of about 4.65 MWth with the drinking water network–playing the role of low temperature heat source -as an alternative to conventional fossil fuel heating. The heat recovery reduces water temperature from 15 °C to 12 °C, thus requiring partial reheating by the drinking water end-user that needs to be estimated to evaluate the energetic convenience of this solution. Heat transfer between water mains and surrounding soil is considered by a proper thermal model computing the temperature vs. time profile at nodes. The developed model, which exploits Epanet to simulate the water network, compares the primary energy consumption and CO2 emissions of the studied system with a conventional district heating solution. Each component, which constitute the overall system, (i.e. heat pump, water network, heating by water end-user etc.) is analyzed and modelled. Assuming a fossil fuel based scenario, the investigated heat pump system reduces the overall primary energy consumption and CO2 emission by about 3%. This value boosts to 41% in case all the electricity generation relies on renewables, thus proving this solution is a promising alternative to conventional district heating in future energy scenarios dominated by renewables. Highlights: A model to study heat recovery from drinking water network is proposed. A detailed thermal model to investigate heat exchange between water pipe and soil is presented. A techno–energetic analysis is developed for a Milan district. Switching from conventional district heating with the proposed system reduces primary energy consumption.